Seasonal variation of the epigeal coleopteran diversity in the Laguna Carén (Santiago, Chile). (2018)
The seasonal variation of epigeal coleopteran diversity and physical-chemical parameters associated to water quality in the Laguna Carén (Santiago, Chile) was evaluated. Different physical-chemical parameters of lagoon water were measured in spring and summer at four random sampling stations, representative of the vegetable coverages. The epigeal coleopterans of the shore were collected by means of interception traps (n = 40), installed at random. It was estimated the abundance and richness of the coleopterans by sampling station and season. In addition, they were separated into trophic guilds: phytophagous, predatory and saprophagous. The differences in abundance and richness were evaluated with nonparametric Kruskal-Wallis tests, followed by Dunn (sampling station) and Mann-Whitney (season) tests. The same statistical procedure was applied to trophic guilds. The ensemble of species of epigeal coleopteran was represented by 19 species (14 natives) from eight families, constitutes the first record of insects in the lagoon. The richness of epigeal coleopteran was significantly higher in spring; while abundance was in summer, concurring with the sampling stations with higher coverages. The availability of food and shelter for epigeal beetles would be influenced mainly by anthropic factors, which lead to a greater degree of fragmentation and alteration of the habitat. The information generated can serve as a basis for future research on bioindicators in vulnerable wetlands in the Mediterranean region.